One‐Pot Synthesis of Doxorubicin‐Bioactive Glass‐Ceramic Hybrid Nanoparticles through a Bio‐Inspired Route for Anti‐Cancer Therapy. Issue 5 (1st February 2023) - Dey, Namit; Santhiya, Deenan; Das, Asmita
Abstract: In this study, we report doxorubicin preparation with bioactive glass‐ceramic as a novel hybrid nanoparticle formulation. Synthesis was carried out through a bio‐inspired route where different precursors of bioactive glass are added to a Tris(hydroxymethyl)aminomethane buffer adjusted to slightly alkaline pH containing doxorubicin. With increasing concentration of doxorubicin, loading increased in quantity with comparatively higher drug release in acidic pH than neutral pH. Without synthetic surfactant or high temperature calcination, bioactive glass‐ceramic nanoparticles demonstrated significantly superior cytotoxic behavior towards osteosarcoma cell line when compared to equivalent free drug or its action towards non‐cancerous cell line. The particles exhibited hydroxyapatite deposition when immersed in simulated body fluid for 7 days. The bio‐inspired route for synthesis of doxorubicin‐bioactive glass‐ceramic hybrid nanoparticles is an efficient cost ‐effective synthesis mechanismwhich is environmentally friendly without hampering the stability or activity of the drug. Abstract : We report one‐pot synthesis of doxorubicin‐bioactive glass ceramic nanoparticles (DOX‐BG) through the bio‐inspired route.In this study, doxorubicin servesas a template for facilitating formation of bioactive glass in presence of Tris(hydroxymethyl)aminomethane buffer (pH 8.5) and is also the chosen cargo for delivery. The obtained DOX‐BG nanoparticles are bioactive in nature and exhibit effective anti‐cancer activity against bone cancer cell line.